Kelimpahan dan Keanekaragaman Spesies Kupu-Kupu (Lepidoptera; Rhopalocera) Pada Berbagai Tipe Habitat di Hutan Kota Muhammad Sabki Kota Jambi The Richness and Diversity of Butterflies (Lepidoptera; Rhopalocera) in the Urban Forest of Muhammad Sabki, Ja - Sri Estalita, RAHAYU (Universitas Jambi, 2012)
ABSTRACT. Species diversity of butterflies (Lepidoptera; Rhopalocera) of the urban forest of Muhammad Sabki, Jambi were studied from January to February 2012. The urban forest was divided into four different habitat types: the Park, the Stream side, the Rubber forest, and the Mixed forest. Two transect routes were established for each habitat type. Observations were made on the number of individuals of each species of butterflies found within the transects. Data were analyzed by Shannon-Wiener, Evenness, and Sorenson indices. A total of 43 species with 3241 individuals of six families (Hesperiidae, Papilionidae, Nymphalidae, Lycaenidae, and Riodinidae) of butterflies were recorded. Nymphalidae was the most dominating family with the highest species richness at the urban forest. The highest number of butterfly species was recorded at the Rubber forest and the Stream side (37 species each), followed by the Park (33 species) and the Mixed forest (27 species). The most abundant butterflies were found at the Rubber Forest, and the least were in the Stream side. Two species (Eurema hecabe and Mycalesis janardana) were observed consistently at all habitat types, and the former was the most abundant species. The highest species diversity and evenness indices were found in the Rubber Forest, while the lowest were in the Stream Side. Species diversity and evenness indices of butterflies of the urban forest can be categorized as low and low to moderate respectively. Key words: abundance, butterfly, Jambi, species, diversity, richness, urbanforest. ABSTRAK.Penelitian mengenai keanekargaman jenis kupu-kupu(Lepidoptera; Rhopalocera) dilakukan di Hutan Kota Muhammad Sabki, dari Bulan Januari s/d Februari 2012. Hutan kota tersebut terdiri dari empat habitat yaitu taman, pinggir kolam, hutan karet, dan hutan campuran. Pada masing-masing habitat tersebut dibuat dua transek. Pengamatan dilakukan untuk mengetai jumlah individu kupu-kupu pada masing-masing transek. Data yang diperoleh dianalisis menggunakan Indek Shannon-Wiener, kemerataan (Evenness), dan Indeks Sorenson. Jumlah individu kupu-kupu yang diperoleh sebanyak 3241 jenis yang terdiri dari 43 spesies yang berasal dari 6 famili (Hesperiidae, Papilionidae, Nymphalidae, Lycaenidae, and Riodinidae). Nymphalidaemerupakan famili yang paling dominant serta merupakan famili yang memiliki kekayaan jenis yang tertintggi di hutan kota tersebut. Jumlah spesies yang paling tinggi ditemukan pada habitat hutan karet dan pinggir kolam (masing-masing 37 spesies), selanjutnya pada habitat taman (33 spesies) dan hutan campuran (27 spesies). Famili kupu-kupu yang paling melimpah terctat di hutan karet, sedangkan yang paling rendah di pinggir kolam. Dua spesies yang secara konsisten ditemukan pada semua habitat yaituEurema hecabedanMycalesis janardana, spesies yang kedua merupakan jenis yang paling melimpah. Indek kemerataan dan keanekaragaman jenis yang plaing tinggi ditemukan di hutan karet, sedangkan yang paling rendah pada habitat di pinggir kolam. Indeks keanekaragaman dan kemerataan jenis kupu-kupu pada hutan kota tersebut masing- masing termasuk dalam kategori rendah dan rendah sampai sedang. Kata kunci :kelimpahan, keanekaragaman, kekayaan, jenis, kupu-kupu,Jambi,hutan kota